The Patriarchal Paradigm in Migration: The Social Challenges of the Serbian Family in Hungary After the Great Migration - Borál, Szvetlána (Migrations in the Slavic Cultural Space. From the Middle Ages to the Present Day, 2022)
Inhabiting the Upper Danube in Hungary after the Great Migration of 1690, Serbs and other Balkan peoples brought not only the culture and tradition of their homeland, but also a kind of patriarchal pattern that was deeply rooted in all social and private spheres of immigrant life. No laws, threats or punishments could change this patriarchal paradigm, and customary rules was above the law. Although many changes in family life and the position of women have been visible since the third decade of the 18th century, most of the harmful customs continued to be practiced in the later period. In this paper, we deal with family conflicts among Serbian immigrants, which are reflected in intergenerational conflicts, the harsh customary right of parents to sell girls for marriage and its consequences, as well as gender inequality.